2018
DOI: 10.1002/arp.1727
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical prospection and archaeological excavation of ancient iron smelting sites in the Barun‐Khal valley on the western shore of Lake Baikal (Olkhon region, Siberia)

Abstract: In 1997, an ancient iron production site, Barun-Khal 2, was discovered in the Barun-Khal valley (Olkhon region, near the west shore of Lake Baikal). This discovery initiated studies of the archaeometallurgical potential of the valley. They included magnetometry, resistivity, self-potential (SP) and radiometric surveys, archaeological excavation, analysis of chemical composition and magnetism of slag and other residuals, and radiocarbon dating of charcoal samples. As expected, the most efficient was the magneto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The amount of slag found during excavation is rather small, up to 1 kg in weight, as well as amount of clay pottery fragments (few pieces only). When compared to slag volumes (up to hundreds of kilograms) in the neighboring metallurgical sites of Kurma and Barun-Hal, where iron production has been operating for several centuries [11,12], the small slag amount at East Hungai indicates that only single, probably, trial iron smelting was run here.…”
Section: The Scale Of Iron-smelting Activity In East Hungai Sitementioning
confidence: 96%
See 1 more Smart Citation
“…The amount of slag found during excavation is rather small, up to 1 kg in weight, as well as amount of clay pottery fragments (few pieces only). When compared to slag volumes (up to hundreds of kilograms) in the neighboring metallurgical sites of Kurma and Barun-Hal, where iron production has been operating for several centuries [11,12], the small slag amount at East Hungai indicates that only single, probably, trial iron smelting was run here.…”
Section: The Scale Of Iron-smelting Activity In East Hungai Sitementioning
confidence: 96%
“…to the first half of the first millennium A.D by the analogy with metallurgical sites of Kurma and Barun-Hal [11][12]. These sites are located on the opposite shore of Lake Baikal in front of the East Hungai (Figure 1).…”
Section: Site Description and Samplingmentioning
confidence: 99%
“…This led to a cessation of granitic deposits from the nearby Primorsky Range (Kozhevnikov et al, 2018). This change enabled soil accumulation and vegetation growth over the granitic material, which, due to attenuation by the soil, was characterized by a notable reduction in radioactivity (Kozhevnikov et al, 2018). In a separate study, preliminary findings from Bezuidenhout (2012) suggest that historic human activity at a site may be characterized by a depletion in potassium concen- 1.2 | Previous applications of gamma spectrometry in archaeology…”
Section: A New Geophysical Toolmentioning
confidence: 99%
“…Some studies have suggested that gamma radiation data can provide valuable insight into the geoarchaeological context of a site. For example, Kozhevnikov et al (2018) highlighted the value of collecting gamma ray measurements alongside traditional geophysical data during the survey of ancient iron smelting sites in Siberia. In this study, radiation data supported the identification of a rapid change in climatic and/or hydrogeological conditions at the site.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional geophysical iron exploration methods, magnetometric and radiometric data had to be collected directly in all parts of the region to identify mineral anomalies [28][29][30]. Collecting magnetometric and radiometric data directly requires a lot of time and cost [31].…”
Section: Introductionmentioning
confidence: 99%